Polymer Electric Conductor as Means for Reduction of Power Expenses - V. P. Lysov; R. A. Mineev; D. M. Pikus (Наука и техника)
The paper gives results of the investigations and established interrelations of electrical engineering and heat engineering indices while applying heating polymer wires and reveals their application as an energy saving meansю